Blended Learning Models for Secondary Education: Bridging Traditional Pedagogy and Digital Transformation - Jie, Wei (International Conference on Fundamental and Applied Research (I-CFAR), 2026)
The use of digital technologies in education increasingly transforms educational practices while also revealing persistent inequities in access and participation. In elementary schools and middle schools, having unfair amounts of devices and the internet can prevent good learning. This particular study helps to show economically and socially dangerous grade disparities between white and non-white communities. Blended learning models combine traditional and contemporary pedagogical styles to enhance student learning. The research will examine if such tools increase accessibility, engagement, and learning outcomes or give rise to new issues such as digital inequality and difficulty of teaching, etc., in the secondary education sector. In this study, the researcher used data that had already been published by experts in the field. Secondary sources are used for the collection of sufficient data related to the research area. Current articles from the last five years are used to address information. They discovered that it was harder for teachers to give good quality education. In fact, schools with more developed educational programs have greater success in teaching technology. Closing the gap between people with and without technology is a long-term process. Effective interventions should include training for digital components of learning as well as tools to ensure broader access to it. Accomplishing digital equality will require all parties composing an educational system to collaborate with a goal in mind. The research offers many benefits to educators. It gives them more knowledge and helps improve learning. Addressing this challenge is crucial because it benefits education globally. The findings of the research will show the ways through which future teachers can incorporate technology for the growth of education by minimizing the negative impact on students.